EFEKTIVITAS KONSELING REALITA UNTUK MENINGKATKAN RESILIENSI AKADEMIK PADA SISWA DI SMK NEGERI 1 SAMARINDA - BR Ginting, Agelita; Sari Pratiwi, Yashinta (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Basically, students face numerous demands, both academic and non-academic. However, vocational high school (SMK) students differ slightly from general high school (SMA) students, as SMK students are expected to master practical skills and competencies relevant to the workforce, in addition to possessing adequate supporting knowledge. Due to the multitude of demands, SMK students, in particular, are prone to experiencing academic stress. Therefore, high academic resilience is required to overcome academic stress, which could otherwise hinder students' ability to adapt to future industry demands. The purpose of this study is to analyze the effectiveness of group counseling using the WDEP technique in enhancing students' academic resilience. The research was conducted on eleventh-grade students at SMK Negeri 1 Samarinda. This study employed an experimental research design with a one-group pretest-posttest approach, in which a single group served as the experimental group receiving group counseling treatment using the WDEP technique. Purposive sampling was used to select eight students as participants in the group counseling sessions. Data analysis was performed using parametric statistics, specifically the paired sample t-test and N-Gain Score test, with the aid of SPSS 26 software. The results indicated a significant improvement in students' academic resilience levels, with the average score increasing from 96.75 in the pretest to 147.625 in the posttest. Hypothesis testing revealed a significance value of 0.000 (< 0.05), and the N-Gain Score analysis yielded a result of 51.157%, indicating that reality group counseling with the WDEP technique is effective in improving students' academic resilience.